"Cell adhesion resistant, UV curable, polymer zinc oxide nanocomposite materials for intraocular lens application". (19th December 2017) - Syed Hussain, Shaik; Donempudi, Shailaja; Tammishetti, Shekharam; Garikapati, Koteswara Rao; Bhadra, Manika Pal
Abstract : Foldable acrylic lenses are used for surgical replacement of diseased intraocular lens in treatment of cataract. One of the main postsurgical complications of this treatment method is postcapsular opacification caused by proliferating epithelial cells. The most common approach taken by research community to address this issue has been modification of lens surface with hydrophobic or hydrophilic moieties to manipulate surface cell interaction. In the present study, inherently cell repellent photopolymer resins are presented. Taking advantage of zinc oxide antiproliferative properties, its nanocomposite resins were made and investigated. Hydrophobically modified zinc oxide nanoparticles and poly(phenylethylacrylate‐co‐phenylethyl methacrylate) were made, and their nanocomposite films were prepared by UV polymerization. Films made with 5 wt% ZnO nanoparticles in them resisted fibroblast attachment substantially. In addition, these films filtered harmful UV light and showed other necessary properties like visible light transparency, glass transition temperatures, mechanical strength, and biocompatibility necessary for making intraocular lenses.